Analisis Indeks Kepuasaan Masyarakat Terhadap Pelayanan Balai Pengobatan Pada Malam Hari Di Puskesmas Manukan Kulon Surabaya - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; Yulis Setyowati; Suprayoga Suprayoga (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2011)
This research to know public satisfaction index to services at night clinic at the health center, by applying the principles set forth in Kepmenpan Service No. KEP/25/M.PAN/2/2004 on community satisfaction index, which includes 14 elements. Type of study was a descriptive quantitative research. Sampling Sampling uses incidental and gained 100 people. Retrieving data with the distribution of questionnaires to the respondents. To analyze the data using the General Guidelines for Preparation of SME Kepmenpan No. 25 of 2004.Based on research results generated that element of service procedures to get the highest score with a total average value per element of 3.28 with the quality of services Excellent. The index of community satisfaction with clinic services unit at the health center Manukan Kulon get a value of 77.51 with good service quality. People's satisfaction levels of service in the evening clinic at the Puskesmas Manukan Kulon is Satisfied.